2013
DOI: 10.1007/s13277-013-0767-2
|View full text |Cite
|
Sign up to set email alerts
|

The −590C/T polymorphism in the IL-4 gene and the risk of cancer: a meta-analysis

Abstract: Interleukin-4 (IL-4) plays an important role in the pathogenesis of cancer. The -590C/T polymorphism in the IL-4 gene has been implicated in susceptibility to cancer, but the results have been inconclusive. The aim of this study was to analyze the association between this polymorphism with the risk of cancer by meta-analysis. PubMed, Embase, CNKI, and Wanfang databases were searched for all publications concerning the association between this polymorphism and cancer risk. Statistical analyses were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Despite distinct allele and genotype frequencies, the negative association with GC is, however, consistent among different populations. Our finding is also validated in a meta-analysis that pooled all existing studies for association analysis for cancer risk and subgroup analysis for GC (Zhang et al, 2013). What is noteworthy is that a higher risk of developing diffuse type (OR, 1.64; 95%, CI 1.01-2.67) or cardia cancer (OR, 2.44, 95%CI 1.13-2.67) was observed for the CT/CC genotype in Chinese Taiwan, which is contradictory to our result for subgroup analysis (Wu et al, 2003).…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiosupporting
confidence: 67%
See 1 more Smart Citation
“…Despite distinct allele and genotype frequencies, the negative association with GC is, however, consistent among different populations. Our finding is also validated in a meta-analysis that pooled all existing studies for association analysis for cancer risk and subgroup analysis for GC (Zhang et al, 2013). What is noteworthy is that a higher risk of developing diffuse type (OR, 1.64; 95%, CI 1.01-2.67) or cardia cancer (OR, 2.44, 95%CI 1.13-2.67) was observed for the CT/CC genotype in Chinese Taiwan, which is contradictory to our result for subgroup analysis (Wu et al, 2003).…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiosupporting
confidence: 67%
“…Of three common polymorphisms in the IL8 gene, the T-to-A base substitution at -251 (T-251A, rs4073) of the promoter region is associated with increased IL-8 production (Hull et al, 2000). To date, although multiple studies have been conducted on association of IL4-590 C>T (Loh et al, 2009;Sugimoto et al, 2010;Zhang et al, 2013) and IL8-251 T>A (Gianfagna et al, 2008;Gao et al, 2010;Liu et al, 2010;Wang et al, 2010;Persson et al, 2011;Yuzhalin, 2011;Wang et al, 2012;Xue et al, 2012) and GC among Asians, Caucasians and Hispanics, results are hardly conclusive with evident variability according to race. Even within the Chinese population, studies report conflicting results among studies in Taiwan (Wu et al, 2003;Lai et al, 2005;Lee et al, 2005), Fujian (Lin, 2008), Hebei (Zhang et al, 2010), Beijing (Lu et al, 2005), Guangdong and Shanxi (Zeng et al, 2005) for each polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 2 years, two meta-analyses investigated the association. 9 , 10 Interestingly, the conclusions of the two previous meta-analyses were contradictory. In addition, more case–control studies have been published during these past 2 years.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies showed that the frequency of rs3814055 in the NR1I2 gene varied according to different populations. The frequency of this variation in a Chinese Han population was 0.218 (Wang et al, ), 0.39 for Caucasians (Zhang et al, ), 0.21 for Asians (King et al, ), 0.50 for Europeans (King et al, ), 0.36 for the Dutch (Bosch et al, ), and 0.34 for African Americans (Thomas et al, ). In our previous studies, the frequency of the rs3814055 SNP variant in the Lhoba population and in the Miao population were 0.101 and 0.09 (He et al, ; Jin, Aikemu et al, ), respectively.…”
Section: Discussionmentioning
confidence: 99%